Emotions and Disclosures: Calm versus Frustrated States - Themistocleous, Christos (My University, 2023)
This research investigates emotions and their influence on disclosure decision-making. The paper is interested in the impact of the visceral states (Loewenstein, 2000) on disclosure risk-benefit assessments and whether frustration influences divulgence on three fronts. First, whether frustrated individuals over-disclose or clam-up compared to calm ones. Secondly, whether frustration will affect the accuracy of assessments in relation to contextual relevance when requested to disclose new information. Lastly, whether frustration leads to greater reliance on default settings pertaining to consent of data use or customisation, where the latter signals consent to less data uses. Hypotheses are tested using experiments with the treatment group subjected to the frustration-inducing exercise prior to the disclosure assessment segment. Through this examination, the present study investigates emotions, and specifically frustration, and how it can amplify imperfect rationality for divulgence thus positioning consumers in risky, vulnerable disclosure situations.
Keywords: Information Disclosure; Nudge Theory; Emotions; Sludge